Effect of Varying Nutrient Density of Diets on Productive Performance in Dahlem Red Layers - Prakash, Bhukya; Rao, S.V. Rama; Raju, M.V.L.N.; Verma, S. K.; Panda, A. K. (Indian Journal of Animal Nutrition, 2019)
The study was conducted to optimize the nutrient requirement for Dahlem Red (DR) birds. Five diets were formulated Â i.e., one basal diet (BD) with optimum (100%) nutrients, two diets with lower (97.5 % and 95%) and two diets with higher (102.5% and 105%) nutrients to the BD. A total of 240 number of DR layers of 23 weeks were selected and divided into 5 groups, each having 8 replicates and each replicate had 5 birds. The experiment was continued up to 70 weeks. Feed intake was higher (P<0.05) in groups fed the diet contained 95 and 97.5% of nutrient of the BD.Â The egg production and egg weight were higher (P<0.05) in groups fed the diet contained higher nutrient (102.5% and 105%) compared to those birds fed lower nutrient based-diets (97.5 % and 95%) during the 23-42 weeks. The feed efficiency was better (P<0.05) among the groups fed diet contained higher nutrient density diets compared to those groups fed lower nutrient density diets during the 23-42 and 59-70 weeks. However, egg components and egg quality parameters did not differ among the groups fed the different experimental diets. Therefore, it is concluded that the diet with 102.5% nutrients probably the more remunerative as the higher egg production and better feed efficiency was evident.